2013
DOI: 10.1021/jo302228w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Picket Porphyrin Receptors That Bind Phosphatidylglycerol, an Anionic Phospholipid Found in Bacterial Membranes

Abstract: The lipid binding ability of four urea-picket porphyrins designed to bind to both the phosphate anion portion as well as the glycerol hydroxyl groups of phosphatidylglycerol (PG) has been investigated. Isothermal titration calorimetry (ITC) and (1)H NMR were used to determine the receptor's stoichiometry of binding, association constants, and both the enthalpy and entropy of binding with the PG anion. Spectral evidence shows that the phosphate anion portion of PG is hydrogen bonded to the urea groups of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Human blood plasma samples were purchased from Helena Biosciences Europe (UK). Polyethylene glycol substituted by an amine terminal group (PEG-NH2), namely 2-[2-(2-ethoxyethoxy)ethoxy] ethylamine (Alliband et al, 2013) and 2-(tert-butoxycarbonyl-aminooxy) acetic acid (Miller et al, 2005) were synthesized according to the reported procedures.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Human blood plasma samples were purchased from Helena Biosciences Europe (UK). Polyethylene glycol substituted by an amine terminal group (PEG-NH2), namely 2-[2-(2-ethoxyethoxy)ethoxy] ethylamine (Alliband et al, 2013) and 2-(tert-butoxycarbonyl-aminooxy) acetic acid (Miller et al, 2005) were synthesized according to the reported procedures.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The de novo design of our receptors was based entirely on modeling analysis, which demonstrated that the four pickets on the meso-phenyl rings of a porphyrin scaffold, appropriately functionalized, formed a complementary binding pocket to the lipid's multifunctional headgroup. 12 A synthetic advantage to the porphyrin structure is the inherent symmetry of the four pickets that are capable of alignment with the two different sets of lipid functional groups. Our initial studies showed that this was true for ureapicket porphyrins 1 when the pickets were relatively bulky and therefore conformationally rigid (only porphyrins with stable all-α atropisomers would bind to PG in a well-behaved 1 : 1 stoichiometry) (Fig.…”
Section: Preparation and Solution Lipid Binding Ability Of Ammoniumpi...mentioning
confidence: 99%
“…20 The average value of the binding constants taken from three titration experiments (each of which used an average determined from the movement of 2 proton resonances) was 4900 M −1 (Table 1). Upon reverse titration of the lipid with 4b the glycerol protons (multiplets between 3.35-3.85 ppm 12 ) moved upfield during complex formation, indicating the glycerol headgroup lies directly above the ring (S-Fig. 19 †).…”
Section: Preparation and Solution Lipid Binding Ability Of Ammoniumpi...mentioning
confidence: 99%
See 2 more Smart Citations